Alström syndrome with liver cirrhosis: First case from Turkey - Murat BIYIK; Ramazan UÇAR; Gökhan GÜNGÖR; Özlem ÖZER ÇAKIR; Hasan ESEN; Serkan AKSAN; Hüseyin ATASEVEN; Ali DEMİR (Turkish Journal of Gastroenterology, 2019)
-